2008
DOI: 10.1002/imhj.20197
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms following childbirth and mothers' perceptions of their infants

Abstract: Postpartum psychological distress can adversely affect the early mother-infant relationship; however, this has not been investigated in relation to posttraumatic stress disorder (PTSD) following childbirth. This article explores whether PTSD symptoms relating to labor and delivery are associated with mothers' early perceptions of their infant. Using labor and childbirth as the stressor criterion, 211 women were assessed at 6 weeks' postpartum for symptoms of intrusions, avoidance, and hyperarousal. Their perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 44 publications
4
109
0
8
Order By: Relevance
“…Although maternal psychological health in the present study was within a normal range for a community sample (see, Condon & Corkindale, 1998;Crawford, Henry, Crombie & Taylor, 2001;Davies et al, 2008;Jones et al, 2013;Tennant et al, 2007), maternal mood was negatively correlated with perceived mother-infant attachment (see also Davies et al, 2008). This correlation suggests that perceived mother-infant attachment might be a more appropriate measure of the mother-infant relationship than maternal perceptions of their infant's warmth and invasiveness used by Jones et al, (2013).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Although maternal psychological health in the present study was within a normal range for a community sample (see, Condon & Corkindale, 1998;Crawford, Henry, Crombie & Taylor, 2001;Davies et al, 2008;Jones et al, 2013;Tennant et al, 2007), maternal mood was negatively correlated with perceived mother-infant attachment (see also Davies et al, 2008). This correlation suggests that perceived mother-infant attachment might be a more appropriate measure of the mother-infant relationship than maternal perceptions of their infant's warmth and invasiveness used by Jones et al, (2013).…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, the mother-infant relationship is affected by maternal symptoms of PTSD (Davies, Slade, Wright & Stewart, 2008;McDonald, Slade, Spiby & Iles, 2011) and PND (Edhborg, Lundh, Seimyr & Widstorm, 2001;Murray, 1992;Murray, Fiori-Cowley, Hooper & Cooper, 1996;Taylor, Atkins, Kumar, Adams & Glover, 2005). Thus, it is important to consider the role of a variety of maternal emotional responses, in relation to infant face interest, within general community samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, some argue that this association may be due to negative parental perceptions rather than a true objective judgement of the child's character (Pauli-Pott, Mertesacker, Bade, Haverkock, & Beckmann, 2003). Davies, Slade, Wright and Stewart (2008) similarly found that mothers with PTSD following childbirth perceived their baby's temperament as more difficult accompanied by more negative maternal representations and less optimal mother-infant relationship. Similar to other areas of research, studies have focused on mothers only, with limited research into the association between father's mental health and perceptions of their infant's temperament, and the parent-baby relationship.…”
Section: Baby Characteristicsmentioning
confidence: 99%
“…For adolescents, the total scale demonstrates an internal reliability of 0.60 to 0.90 with events other than childbirth. Previous use of the IES exploring childbirth trauma among adults (Creedy, 1999;Davies, Slade, Wright, & Stewart, 2008) has noted reliabilities between .80 and .90 (Creedy, 1999). Reliability for this sample of adolescents was established at .82.…”
Section: Sampling and Settingmentioning
confidence: 80%